Quality of Life and Nutritional Status of the Geriatric Population of the South-Central Part of Nepal - Sabita Sharma; Dipendra Kumar Yadav; Isha Karmacharya; Raju Pandey (Journal of Nutrition and Metabolism)
Background. The main objective of the study was to assess the nutritional status and quality of life in the geriatric population of Lahan municipality of Siraha district. Methods. A cross-sectional analytical study was conducted in Lahan municipality of Siraha district from June to December 2017. The Mini-Nutritional Assessment tool was used to investigate the nutritional status, and World Health Organization Quality of Life-OLD questionnaires were used to assess the quality of life among geriatric population. Result. Out of the total participants, one-third (45.7%) of the participants were at risk of malnutrition and 19.8% were malnourished while 34.5% had normal nutritional status. It was seen that 48.2% of participants had good quality of life whereas 51.8% of them had poor quality of life. There was a significant association between nutritional status and quality of life in the elderly population. Conclusion. The findings showed the need for active ageing interventions to improve the nutritional status and quality of life of elders at the community settings. Proper attention should be focused on elders’ nutrition to reduce the observed prevalence of malnutrition, and focus should be given on the nutrition status that leads to improve the quality of life of elders.